Are we there yet? - Santat, Dan. (New York : Little, Brown and Co., 2016)
A boy goes on a long car ride to visit his grandmother and discovers time moves faster or slower depending on how bored he is.
School Library Journal, January 2016.
Booklist starred, February 2016.
Pub Weekly, January 2016.
Kirkus Starred, February 2016.
Horn Book, March 2016.
Bulletin (Center for Children's books), April 2016.
Keywords: Space and time -- Juvenile fiction; Automobile driving -- Juvenile fiction; Space and time -- Fiction; Automobile driving -- Fiction; Space and time -- Fiction; Automobile drivers -- Fiction; Space and time -- Fiction; Automobile driving -- Fiction; Boredom -- Fiction